Understanding Political Narratives: Word Cloud Analysis of Yoon Seok-Yeol's Impeachment - Sinta Rahmadani; Imam Yuadi (Dinasti Research, 2025)
This study uses computational text analysis to analyze political rhetoric in the context of the impeachment of South Korea’s former president and chief prosecutor Yoon Seok-yeol. This Project analyzes statements of ten different international media outlets a month prior to the impeachment held in December 2024 through nexus tools within multi dimensional scaling and word clouds. The study illuminates startling issues South Korea is currently grappling with, and how stark the media’s influence is on public perception by exhibiting political themes such as “impeachment”, “martial law”, “opposition” and “party”. A distance matrix and MDS plot aids in understanding the correlation between public issues, the legal angle and issues regarding partisan divides. Such conversations can now be segmented into core narratives in lieu of these visuals, and Cohen easily be elaborated through computational models which highlight which topic or idea is popular in the public eye. The findings are commensurate with the literature discussing the role of public and media sentiment in impeachment process and suggest the opportunities of coupling qualitative and computer approaches. The research offers a technique on how to evaluate political narratives which would aid in enhancing the communication sought by the Penn State University Department of Communication in the governance of the society and democratic processes.